2014
DOI: 10.1038/tp.2014.120
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin-N-acetylserotonin–melatonin pathway as a biomarker for autism spectrum disorders

Abstract: Elevated whole-blood serotonin and decreased plasma melatonin (a circadian synchronizer hormone that derives from serotonin) have been reported independently in patients with autism spectrum disorders (ASDs). Here, we explored, in parallel, serotonin, melatonin and the intermediate N-acetylserotonin (NAS) in a large cohort of patients with ASD and their relatives. We then investigated the clinical correlates of these biochemical parameters. Whole-blood serotonin, platelet NAS and plasma melatonin were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 69 publications
7
143
0
1
Order By: Relevance
“…4, path B, as “melatonin” only). This confirms previous assessments performed in plasma or urine [10, 4952], while lending further support to blunted melatonin synthesis possibly due to reduced ASMT enzyme activity in ASD [53, 54]. Melatonin is synthesized and released by the pineal gland into the systemic circulation and readily passes the blood-brain barrier [55].…”
Section: Discussionsupporting
confidence: 85%
“…4, path B, as “melatonin” only). This confirms previous assessments performed in plasma or urine [10, 4952], while lending further support to blunted melatonin synthesis possibly due to reduced ASMT enzyme activity in ASD [53, 54]. Melatonin is synthesized and released by the pineal gland into the systemic circulation and readily passes the blood-brain barrier [55].…”
Section: Discussionsupporting
confidence: 85%
“…Several studies [150][151][152] , which have not all been replicated 153 , have reported an increase in BDNF levels in the blood of patients with ASD. In addition, high plasma levels of serotonin and N-acetylserotonin, as well as low plasma levels of melatonin, are more frequently observed in individuals with ASD than in controls 154,155 . Given that N-acetylserotonin is a potent agonist of the BDNF receptor tropomyosin-related kinase B (TRKB; also known as NTRK2) 156 , an excess of this molecule could increase TRKB-induced phosphoinositide 3-kinase signalling, thus leading to higher protein synthesis, similarly to the effect of mutations affecting regulators of the mTOR pathway.…”
Section: Synaptic Homeostasis and Asdsmentioning
confidence: 99%
“…The primary metabolite of serotonin, 5-HIAA, is also increased in the urine in a few ASD studies, with little evidence that there is altered metabolism of 5-HT (Hanley et al, 1977b, Minderaa et al, 1994, Mulder et al, 2010). Interestingly, one study reported that N-acetylserotonin (NAS), which is a precursor in melatonin synthesis, is also increased in ASD, but neither NAS nor melatonin show a correlation with 5-HT levels despite a robust negative correlation between NAS and melatonin levels (Pagan et al, 2014). …”
Section: Potential Mechanisms Of Hyperserotonemiamentioning
confidence: 99%